Housing Market : A Bibliometric Analysis from 2020 to 2024 - Abdul Hayy Haziq, Mohamad; Rossazana, Ab-Rahim; Abdul Rahman, Edruce Kushair; MOHD SUFFIAN, MOHAMED ESA (Human Resource Management Academic Research Society, 2024)
The housing market can be reflecting as a barometer of economic health. There are numerous studies focus on the housing market, reflecting its significance as a crucial asset for households. This study seeks to perform scientific mapping and an extensive bibliometric analysis concerning the housing market, utilizing data from the Scopus database from 2020 until 2024. The finding of this study the most influence article related to housing market is “Do short-term rental platforms affect housing markets? Evidence from Airbnb in Barcelona” study by Garcia-López et al. (2020). This study also identified that China, United States, and United Kingdom emerge as the predominant nations contributing significantly to the body of literature in the field of the housing market and "Sustainability” journal under the Multidisciplinary Digital Publishing Institute (MDPI), stands out as the most active and prolific publisher in the housing market keyword.